Penerapan Desain UI/UX Pada Aplikasi Buku Kas Laundry Menggunakan Metode Lean Ux - Nabawi, M Reza; Wulandari, Fitri; Safaat, Nazruddin; Darmizal, Teddie (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Laundry services are businesses in the field of washing and drying services, especially clothes. This business is growing as the number of consumers who use laundry services increases, because it can help make things easier for busy people in their daily work. Using laundry services can be used as an alternative way to help with their clothes washing activities. With digital developments, laundry owners have started using cash book applications to make their work easier, such as recording orders, recording expenses and recording income. However, the cash book recording carried out in the cash book application is currently done manually, Previous users have used existing applications, because users feel uncomfortable with the appearance, such as colors that are uncomfortable to look at, fonts that are too small and menu buttons that are confusing. So that it encourages researchers to make a redesign of the application design. Based on these problems, a redesign of the laundry cash book application is needed which can provide comfort for users who will use the application. The method used to solve these problems uses the Lean Ux method. Using the Lean Ux method will make it easier for the author to get feedback faster. Designing a prototype laundry cash book application with an emphasis on User Interface (UI) and User Experience (UX) is the aim of this research. This research uses four stages of the Lean UX methodology, namely Declare Assumptions, Create a Minimum Viable Product, Run an Experiment and Feedback and Research to develop problem assumptions, prototype design, internal experiments and usability testing. Using the System Usability Scale approach, a prototype was created using the Adobe XD program with 20 respondents who received a score of 87 with adjective ratings excellent.